CHALLENGES IN TEACHING ACADEMIC WRITING TO EFL LEARNERS IN HIGHER EDUCATION CONTEXTS - Wijaya, Kristian Florensio (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2026)
It is an indispensable demand for global EFL learners to entrench the comprehensive mastery of exemplary academic writing skills. In concurrence with this underlying principle, second language educators should establish, nurture, and reinforce their learners’ academic writing competencies in the long run to help them achieve fruitful academic success. The researcher conducted this small-scale library study to unravel probable academic writing challenges experienced by EFL learners in higher education contexts. After completing this library investigation, it is hoped that these specifically generated findings will enlighten the perspectives of second language educational stakeholders regarding the crucial need to embed EFL learners with meaningful, innovative, and contextualized academic writing instructional approaches. To fulfill the aforementioned study objective, the researcher capitalized on a thematic analysis method in analyzing particular research results derived from 30 former academic writing challenges in higher education scientific works. With the help of a thematic analysis method, the researcher could yield more comprehensible and applicable findings as each finding was grouped into similar research themes. The thematically-categorized findings revealed some common academic writing hurdles amidst learners’ regular classroom settings, namely linguist, cognitive, strategic, affective, environmental, and pedagogical barriers.